Errors In Writing Descriptive Text Made By The SecondGrade Students Of SMP Negeri 1 Kartasura - SEPTIANA, SEPTIANA (2012)
This research studies about errors in writing descriptive text. The subject of this research is the second grade students of SMPN 1 Kartasura in 2011/2012 academic year. The object of this research is the erroneous on paragraph in descriptive text made by the students. The objectives of this research are (1) to describe the types oferrors, (2) to find out the sources oferrors. In this research, the writer uses descriptive qualitative. The data sources are taken from 30 student's descriptive text written of the second grade of SMP Negeri I Kartasura. The writer collects the data from the students writing activity, and document. The documents of this research are student's work sheets. Here the writer classifies the types of errors by using linguistic category and surface taxonomy. The result of this research shows that; (l) There are 4 levels errors; substance erors at l7,2Yo, grammar erTors at 54,9Yo, lexical effors at l7,7Yo, and discourse errors at l0,2o/o, and classified into 18 errors that derived from 38 types of errors. Based on the finding above, it can be concluded that the students of SMP Negeri I Kartasura still make some errors in their descriptive texts, and the dominant errors is grammar errors, it can be seen by the highest percentage at 54,9yo especially error in bound morpheme -s/-es at 10,60/o, it means that the students still have difficulties in this area, (2) There are 3 sources of errors; first is interlingual transfer, second is intralingual transfer, and third is context learning where the students used some wrong patterns.